The government’s role in moving towards electronic employment: The Kurdistan Regional Government of Iraq as a model for the period (2018-2021) - Jalal Ibrahim, Rabi; Othman Omar, Luqman; Ali Salih, Shiller (Zanco Journal of Human Sciences, 2023)
The e-recruitment experience seems to be a new concept for the Kurdistan Region of Iraq، which is still somewhat far from digital technologies، especially their use in the field of job search and coordination between job seekers and bidders. And the capabilities، skills and qualifications of job seekers for the agencies responsible for employment through the use of information and communication technology. The research used official data available at the Ministry of Labor and Social Affairs of the Kurdistan Regional Government for the period (2018-2021) using the descriptive analytical method. Several conclusions were reached، the most important of which are: The change in the numbers of registered and unemployed people in the general directorates in this way tended to rise with fluctuation in the number of registered economic projects to provide an opportunity for work during the study period.